Profile of Pre-Service Mathematics Teacher’s Algebraic Thinking Based on Systematic-Intuitive Cognitive Style - Ninda Ayu Nur Kusuma; Masduki (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2023)
Algebraic thinking plays an essential role in increasing mathematics problem-solving abilities. In this study, the pre-service mathematics teacher’s (PMTs) ability of algebraic thinking is explored based on a systematic-intuitive cognitive style. This study aims to reveal students' algebraic thinking abilities regarding systematic-intuitive cognitive style. Three components of algebraic thinking were analyzed: arithmetic generalization, functional thinking, and generalization and justification. The research approach is qualitative with a case study method. The subjects were 31 PMTs at one of the private universities in Surakarta District, Central Java, Indonesia. Data collection methods were algebraic thinking tests,  the Cognitive Style Inventory (CSI) questionnaires, and interview protocol. Four subjects, two PMTs for each cognitive style category were interviewed to reveal their algebraic thinking abilities. The results showed that all subjects were able to solve the functional thinking problem correctly. However, for the generalization arithmetics and justification problems, the PMTs abilities are varied. In addition, the finding also showed the different strategies of systematic and intuitive subjects in solving the problems related to algebraic thinking components. PMTs with a systematic cognitive style solve problems systematically and represent the pattern verbally in the form of a table or word, whereas the PMTs with an intuitive cognitive style solve the problem briefly and visually using pictures pattern. In conclusion, there is a relationship between algebraic thinking ability and cognitive style.